Equivalent to represent inertial and primary frequency control effects of an external system. Issue 14 (7th August 2017) - Weckesser, Tilman; Van Cutsem, Thierry
Abstract : This study presents a novel equivalent, which is suitable for simulation of inertial and primary frequency control effects. In the model reduction procedure, dynamic power injectors are used to replace the external system and to mimic its dynamic behaviour. The parameters of the equivalents are tuned with a simple approach presented in this study. The effectiveness of the proposed method is demonstrated on a modified version of the European Network of Transmission System Operators for Electricity (ENTSO‐E) dynamic study model. The results show that the system frequency response of the unreduced system is retained and a speedup of the simulations of around 4.0 is achieved.